2016
DOI: 10.1186/s12951-016-0190-0
|View full text |Cite
|
Sign up to set email alerts
|

Iron oxide nanoparticles for neuronal cell applications: uptake study and magnetic manipulations

Abstract: BackgroundThe ability to direct and manipulate neuronal cells has important potential in therapeutics and neural network studies. An emerging approach for remotely guiding cells is by incorporating magnetic nanoparticles (MNPs) into cells and transferring the cells into magnetic sensitive units. Recent developments offer exciting possibilities of magnetic manipulations of MNPs-loaded cells by external magnetic fields. In the present study, we evaluated and characterized uptake properties for optimal loading of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
102
0
12

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 124 publications
(122 citation statements)
references
References 41 publications
8
102
0
12
Order By: Relevance
“…Results demonstrated the presence of O-ION inside A172 cells at all conditions tested. In accordance with our results, significant ION uptake was previously reported in rat primary astrocytes (Geppert et al 2009;Hohnholt et al 2010;Geppert et al 2011;Hohnholt et al 2013) and in human Fernández-Bertólez et al 2018b) and rat (Marcus et al 2016) neurons under different experimental conditions. LDH release analysis indicated that exposure to O-ION compromised very lightly the membrane integrity of A172 cells.…”
Section: Discussionsupporting
confidence: 93%
“…Results demonstrated the presence of O-ION inside A172 cells at all conditions tested. In accordance with our results, significant ION uptake was previously reported in rat primary astrocytes (Geppert et al 2009;Hohnholt et al 2010;Geppert et al 2011;Hohnholt et al 2013) and in human Fernández-Bertólez et al 2018b) and rat (Marcus et al 2016) neurons under different experimental conditions. LDH release analysis indicated that exposure to O-ION compromised very lightly the membrane integrity of A172 cells.…”
Section: Discussionsupporting
confidence: 93%
“…Presence of the prepared samples (CDs and E@CDs) cells showed retention of the ability of differentiation, such as neurite outgrowth and the complex network formation. Possible reason explained somewhere else . At different time points – 1, 3 and 6 days, through imaging the progress of differentiation of cell was monitored.…”
Section: Resultsmentioning
confidence: 99%
“…The ability of cells to absorb MNPs depends on their growth in the culture medium and the concentration of NPs. Furthermore, the MNPs does not change the morphology of cells . In addition, MNPs have been found to deliver brain‐derived neurotropic factor to cross the BBB…”
Section: Drug Deliverymentioning
confidence: 99%